Country Music Records : a Discography, 1921-1942. - Russell, Tony (Oxford University Press, 2004)
Country Music Records: A Discography, 1921-1942' documents all country music recording sessions from 1921 through to 1942, including unreleased sides. The discography includes alphabetical indexes to all song titles and musicians listed. Research is based on files and session logs from record companies and recording archives.